The role of profits in wage determination: evidence from US manufacturing - Estevão, Marcello (1995)
We estimate the effect of firms' profitability on wage determination for the American economy. Two standard bargaining models are used to illustrate the problems caused by the endogeneity of profits-per-worker in a real wage equation. The profit-sharing parameter can be identified with instruments which shift demando Using information from the input-output table, we create demand-shift variables for 63 4-digit sectors of the US manufacturing sector. The LV. estimates show that profit-sharing is a relevant and widespread phenomenon. The elasticity of wages with respect to profits-per-worker is seven times as large as OLS estimates here and in previous papers. Sensitivity analysis of the profit-sharing parameter controlling for the extent of unionization and product market concentration reinforces our results.